Microsoft Windows XP - June Jamrich Parsons (Thomson Learning, 2002)
Lessons are presented in a two-page layout that combines action steps on the left and large illustrations on the right that show students how their screens should look. Covers both Professional and Home versions of Microsoft Windows XP. Softcover